Linking Hydrobiogeochemical Processes and Management Techniques to Close Nutrient Loops in an Arid River - Bicknell, Kelsey; Regier, Peter; Van Horn, David J.; Feeser, Kelli L.; González-Pinzón, Ricardo (Frontiers in Water, 2020)
In this study, we explored opportunities to optimize food-energy-water (FEW) resources by closing nutrient loops in aridland rivers. We evaluated source and sink behavior of nitrogen as nitrate (NO3-N) in three connected channels associated with an irrigation network, i.e., man-made delivery and drain canals, and the main stem of the Rio Grande river near Albuquerque, New Mexico, USA. All three channels are located downstream of a large wastewater treatment plant that is the main contributor of nutrients to this reach of the Rio Grande. We used a mass balance approach paired with stable isotope analysis to link sources and processing of NO3-N with reaction pathways within the channels over time (a year) and through space (along ~14–53 km reaches). Results indicated that the growing season was an important period of net sink behavior for the delivery channel and the Rio Grande, but the drain channel was a year-round net source. Stable isotope analyses of 15N and 18O found a distinct nitrate signature in the drain associated with biological processing, as well as sites along the Rio Grande impacted by agricultural outflow, but no equivalent signature was present in the delivery channel. Based on our findings, we provide recommendations to help close nutrient loops in our study system and in analogous aridland irrigation networks by (1) minimizing loss during the transfer of nutrients from wastewater facilities to agricultural areas, and (2) minimizing enrichment to downstream aquatic ecosystems by sequestering nutrients that would otherwise escape the nutrient loop.